Pair production by Schwinger and Breit–Wheeler processes in bi-frequent fields. (4th May 2016) - Otto, A.; Nousch, T.; Seipt, D.; Kämpfer, B.; Blaschke, D.; Panferov, A. D.; Smolyansky, S. A.; Titov, A. I.
Abstract : Counter-propagating and suitably polarized light (laser) beams can provide conditions for pair production. Here, we consider in more detail the following two situations: (i) in the homogeneity regions of anti-nodes of linearly polarized ultra-high intensity laser beams, the Schwinger process is dynamically assisted by a second high-frequency field, e.g. by an XFEL beam; and (ii) a high-energy probe photon beam colliding with a superposition of co-propagating intense laser and XFEL beams gives rise to the laser-assisted Breit–Wheeler process. The prospects of such bi-frequent field constellations with respect to the feasibility of conversion of light into matter are discussed.